KORELASI PENGELOLAAN KEUANGAN SEKOLAH DAN KETERSEDIAAN SARANA PRASARANA TERHADAP MUTU LAYANAN PEMBELAJARAN DI SMK NEGERI KABUPATEN MUKOMUKO: KORELASI PENGELOLAAN KEUANGAN SEKOLAH DAN KETERSEDIAAN SARANA PRASARANA TERHADAP MUTU LAYANAN PEMBELAJARAN DI SMK NEGERI KABUPATEN MUKOMUKO - Kusnadi, Engkus; Putri Kartiwi , Asti (Manajer Pendididikan, 2025)
This study examines the relationship between financial management, infrastructure availability, and learning service quality in Mukomuko Vocational High Schools using a quantitative correlational approach. Data from purposively selected teachers were collected via questionnaires and analyzed with multiple linear regression. Findings show that effective financial management enhances learning services through efficient budgeting and better facilities. Adequate infrastructure fosters a conducive learning environment and improves learning effectiveness. Transparent financial management and optimal infrastructure development are key to enhancing vocational education quality